Phosphatase Regenerating Liver3 and ECadherin Expression in Epithelial Ovarian Cancer - Risma Maharani; Syahrul Rauf; Rina Masadah (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To determine the expression of Phosphatase Regenerating Liver-3 (PRL-3) and E-Cadherin in the epithelial ovarian cancer on various stages and differentiation grades. Method: This was a cross-sectional study design conducted at Obstetrics and Gynecology Department of several teaching hospitals, Faculty of Medicine Universitas Hasanuddin from January to June 2015. The expression of PRL-3 and E-cadherin was assessed immunohistochemically in 40 patients with epithelial ovarian cancer including 15 patients in early stage and 25 patients in advanced stage. We used the Fisher’s exact test with the significance of p0.05). The significant difference was found in the expression of E-cadherin whereas the high expression was shown at early stage than advanced stage (p0.05). This study also pointed out no correlation between the expression of PRL-3 and E-cadherin in epithelial ovarian cancer (p>0.05). Conclusion: PRL-3 overexpression does not decrease E-cadherin expression in epithelial ovarian cancer. Keywords: E-cadherin, epithelial ovarian cancer, PRL-3